Toric intraocular lens orientation and residual refractive astigmatism: an analysis - Potvin R (Dove Medical Press, 2016)
Rick Potvin,1 Brent A Kramer,2 David R Hardten,3 John P Berdahl4 1Science in Vision, Akron, NY, 2University of Iowa Carver College of Medicine, Iowa City, IA, 3Minnesota Eye Consultants, Minnetonka, MN, 4Vance Thompson Vision, Sioux Falls, SD, USA Purpose: To analyze intraocular lens (IOL) orientation data from an online toric back-calculator (astigmatismfix.com) for determining if differences were apparent by lens type.Methods: A retrospective review of astigmatismfix.com toric back-calculations that included IOL identification and intended orientation axis.Results: Of 12,812 total validated calculation records, 8,229 included intended orientation and lens identification data. Of the latter, 5,674 calculations (69%) involved lenses oriented 5° or more from their intended position. Using estimated toric lens usage data, the percentage of lenses with orientation ≥5° from intended was 0.89% overall, but the percentage varied significantly between specific toric lens brands (P<0.05). The percentage of back-calculations related to lenses that were not oriented as intended was also statistically significantly different by lens brand (P<0.05). When IOLs were misoriented, they were significantly more likely to be misoriented in a counterclockwise direction (P<0.05). This was found to be due to a bias toward counterclockwise orientation observed with one specific brand, a bias that was not observed with the other three brands analyzed here.Conclusion: The percentage of eyes with lens orientation ≥5° from intended in the Toric Results Analyzer data set was <1% of toric IOLs in general, with the relative percentage of Tecnis® Toric IOLs significantly higher than AcrySof® Toric IOLs. Both of these had higher rates than the Staar® Toric and Trulign® Toric lenses, with the availability of higher Tecnis and AcrySof cylinder powers a likely contributing factor. The AcrySof Toric IOL appears to be less likely than the Tecnis Toric IOL to cause residual astigmatism as a result of misorientation. The Tecnis Toric IOL appears more likely to be misoriented in a counterclockwise direction; no such bias was observed with the AcrySof Toric, the Trulign® Toric, or the Staar Toric IOLs. Keywords: rotation, AcrySof, Tecnis, toric back-calculator, cylinder